2019
DOI: 10.11604/pamj.2019.33.283.17203
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomyxome péritonéal secondaire à une tumeur mucineuse de l’ovaire: à propos d’un cas

Abstract: Le pseudomyxome péritonéal (PMP) ou l'ascite gélatineuse est une entité rare, décrite pour la première fois par R. Wyerth en 1884. Il correspond à une atteinte péritonéale diffuse, composée d'une ascite mucineuse et d'implants épithéliaux mucineux multifocaux. Cette maladie touche essentiellement les femmes. Son incidence est estimée à 2 cas par un million d'habitants. Le pseudomyxome péritonéal peut rester asymptomatique, découvert lors d'une laparotomie. Le symptôme le plus fréquent est représenté par une di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 14 publications
4
13
0
Order By: Relevance
“…Although our case was male, PMP affects women 2 to 3 times more frequently than men. [1][2][3][4][5] Most tumors (90%) are of appendicular origin from low or high grade mucinous appendicular neoplasm and appendicular adenocarcinoma, associated with a mucocele, as in our patient's case. [1][2][3][4][5][6][7] Other tumors are mucinous adenocarcinomas of colonic, gastric, pancreatic, urachal, pulmonary, endocervical or mammary origin, or more rarely mucinous ovarian tumors, cystadenomas or cystadenocarcinomas.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Although our case was male, PMP affects women 2 to 3 times more frequently than men. [1][2][3][4][5] Most tumors (90%) are of appendicular origin from low or high grade mucinous appendicular neoplasm and appendicular adenocarcinoma, associated with a mucocele, as in our patient's case. [1][2][3][4][5][6][7] Other tumors are mucinous adenocarcinomas of colonic, gastric, pancreatic, urachal, pulmonary, endocervical or mammary origin, or more rarely mucinous ovarian tumors, cystadenomas or cystadenocarcinomas.…”
Section: Discussionsupporting
confidence: 59%
“…[1][2][3][4][5] Most tumors (90%) are of appendicular origin from low or high grade mucinous appendicular neoplasm and appendicular adenocarcinoma, associated with a mucocele, as in our patient's case. [1][2][3][4][5][6][7] Other tumors are mucinous adenocarcinomas of colonic, gastric, pancreatic, urachal, pulmonary, endocervical or mammary origin, or more rarely mucinous ovarian tumors, cystadenomas or cystadenocarcinomas. 2,8 Some authors have reported nonneoplastic intraperitoneal mucinous deposits caused by alternative processes such as mucin retention due to a stercolith or diverticulum, or mucinous metaplasia of the fallopian tubes, but such situations are very rare and debatable.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…6 The incidence of PMP was initially proposed to be approximately 1 per million population per year, but this estimate was not based on strong evidence. [1][2][3][4][5][6] Recent Dutch data from Smeenk et al estimated the incidence of mucinous epithelial neoplasms of the appendix to be approximately 0.3% and progression to PMP in approximately 20% of these patients. 1 Extrapolating the data, this places the incidence of PMP at approximately two per million per year.…”
Section: (A) (B)mentioning
confidence: 99%